2008
DOI: 10.1080/00015458.2008.11680332
|View full text |Cite
|
Sign up to set email alerts
|

Rectal Melanoma - a Rare Tumour

Abstract: Malignant rectal melanoma is a rare tumour. We report a case of a 66-year-old man who presented with a two-month history of rectal bleeding, pain, and tenesmus. A semicircular rectal tumour was seen, just above the dentate line. Biopsies proved it to be an amelanotic malignant melanoma, as protein S100, melanoma antigen HMB45 and Melan-A expression were found. CT scan and rectal ultrasound showed invasion into the internal sphincter and several enlarged perirectal nodes. No distant lesions were detected on CT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Few case reports and case series are noted in literature. [ 9 10 11 12 13 ] Studies in primary cutaneous malignant melanoma have shown the superiority of PET and PET/CT over conventional imaging in initial staging and recurrent disease/restaging. [ 14 15 16 17 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few case reports and case series are noted in literature. [ 9 10 11 12 13 ] Studies in primary cutaneous malignant melanoma have shown the superiority of PET and PET/CT over conventional imaging in initial staging and recurrent disease/restaging. [ 14 15 16 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…Few case reports and case series are noted in literature. [9][10][11][12][13] Studies in primary cutaneous malignant melanoma have shown the superiority of PET and PET/CT over conventional imaging in initial staging and recurrent disease/restaging. [14][15][16][17] This study was performed with an aim to calculate the diagnostic performance of PET/CT in initial staging and restaging with suspected recurrence in anorectal melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…The most common complaints are bleeding, rectal pain, tenesmus, and changes in bowel habits. At the histological examination, the presence of protein S‐100, melanoma antigen HMB‐45, and Melan‐A expression are strongly suggestive of melanoma 4. …”
Section: Discussionmentioning
confidence: 99%